View Full Version : linear equations/elimination

babeegirl

11-19-2009, 08:18 PM

help. im 13 and have a test on linear equations/elimination. i need help simplifying.....

5x-2y=-15

2x-2y=-12

this is how far i got

2(5x-2y=-15)

10x-4y=-30

Subhotosh Khan

11-19-2009, 09:44 PM

help. im 13 and have a test on linear equations/elimination. i need help simplifying.....

5x-2y=-15.............................................(1)

2x-2y=-12.............................................(2)

this is how far i got

2(5x-2y=-15)

10x-4y=-30.............................................(3)

Now multiply the equation (2) by 5

5(2x-2y) = 5*(-12)

10x - 10y = -60........................................(4)

Now we subtract (4) from (3) - what do we get?

[spoiler=:3rvogiay]10x - 4y - (10x - 10y) = -30 - (-60)

-4y + 10y = 30[/spoiler:3rvogiay]

Continue.......

babeegirl

11-19-2009, 10:45 PM

[quote="Subhotosh Khan"][quote="babeegirl"]help. im 13 and have a test on linear equations/elimination. i need help simplifying.....

5x-2y=-15.............................................(1)

2x-2y=-12.............................................(2)

this is how far i got

2(5x-2y=-15)

10x-4y=-30.............................................(3)

Now multiply the equation (2) by 5

5(2x-2y) = 5*(-12)

10x - 10y = -60........................................(4)

Now we subtract (4) from (3) - what do we get?

10x - 4y - (10x - 10y) = -30 - (-60)

-4y + 10y = 30

then......

10x-4y=6?

Mrspi

11-19-2009, 11:02 PM

help. im 13 and have a test on linear equations/elimination. i need help simplifying.....

5x-2y=-15

2x-2y=-12

this is how far i got

2(5x-2y=-15)

10x-4y=-30

A good RULE OF THUMB is to look at the equations, and determine what would be the EASIEST way to eliminate one of the variables.

I notice that the y-terms are both -2y...if ONE of the equations had +2y instead of -2y, the y terms would add up to 0, right?

Let's multiply one of the equations by -1. Makes no difference which you do that to...so I'll multiply both sides of the first equation by -1:

-1(5x - 2y) = (-1)(-15)

-5x + 2y = 15

This is our "new and improved" version of the first equation.

Ok...now we have THIS system:

-5x + 2y = 15

2x - 2y = -12

Add those equations together:

-5x +2y = 15

2x - 2y = -12

_______________

-3x = 3

There!!! You have an equation with just one variable. You can solve this equation for x. And when you know what x is, you can substitute that value for x in one of the original equations, and solve for y.

If you're still having trouble with this, please repost and show us all of the work you've done so we can see where your difficulties lie.

Powered by vBulletin® Version 4.2.2 Copyright © 2014 vBulletin Solutions, Inc. All rights reserved.